2015
DOI: 10.1590/1983-80422015233097
|View full text |Cite
|
Sign up to set email alerts
|

Terminalidade da vida infantil: percepções e sentimentos de enfermeiros

Abstract: Objective: To understand the perceptions and feelings of professional nurses towards death and the dying process of children. Methodology: qualitative and exploratory, based on thematic categories. The participants were seven nurses of the Neonatal and Pediatric Intensive Care Unit of a general hospital in the Northwest region of the Rio Grande do Sul (One of the Brazilian States). Data were collected through open questions in the period from February to March 2013 and were submitted to analysis by rating, sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
25

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 16 publications
0
10
0
25
Order By: Relevance
“…A study conducted with 11 nurses from a neonatal and pediatric intensive care unit of a general hospital located in northwestern Rio Grande do Sul revealed how important it is for health professionals to understand what parents are going though so that they can establish clearer and more effective communication to prevent parents from continuing to believe their children will survive in face of the impossibility of cure. The way each family interprets and experiences death is unique and is directly related to their beliefs, context, and history 14 .…”
Section: The First Communication In Exclusive Palliative Carementioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted with 11 nurses from a neonatal and pediatric intensive care unit of a general hospital located in northwestern Rio Grande do Sul revealed how important it is for health professionals to understand what parents are going though so that they can establish clearer and more effective communication to prevent parents from continuing to believe their children will survive in face of the impossibility of cure. The way each family interprets and experiences death is unique and is directly related to their beliefs, context, and history 14 .…”
Section: The First Communication In Exclusive Palliative Carementioning
confidence: 99%
“…For all participants, the communication launched the war against the disease and the various instances of life that it would change; suffering became constant, the uncertainty of the future and the threat of death became part of their everyday lives. Parents also revealed that the relationship between the content of the news and the way it was transmitted made it even worse, as they could perceive through the demeanor of the professional delivering the news the extent of his/ Communication of bad news in palliative care within pediatric oncology her involvement, interest, concern, and commitment towards their children and family members 14 .…”
Section: Feelings Towards Everyday Communication About Exclusive Pallmentioning
confidence: 99%
“…O preparo do profissional de enfermagem é essencial para que o mesmo possa além de desempenhar ações técnicas, gerenciais e assistenciais com qualidade, também possa preservar sua integridade física e também emocional, para que assim, mantenha a qualidade nas ações desempenhadas na sua profissão 6 .…”
Section: Preparo Profissional Para Lidar Com a Perda E Formas De Enfrunclassified
“…A constante exposição à finitude da vida, presenciada pelos profissionais que atuam na área da enfermagem, evidencia a necessidade de que haja reflexões sobre os temores e inseguranças desenvolvidas pelo indivíduo durante o exercício da profissão. A reflexão sobre terminalidade da vida infantil e suas incertezas faz com que o profissional reflita sobre seus sentimentos perante o óbito, desenvolvendo métodos de enfrentamento para lidar com o processo 6 .…”
Section: Introductionunclassified
“…"Na minha pouca experiência em trabalhar dentro de As vivências relatadas aproximam-se da definição desse cuidado, na semelhança de ter uma abordagem ativa que é centrada na qualidade de vida da criança (8) . Entretanto, há uma resistência relacionada à própria condição de desenvolvimento da criança, que implica em constantes mudanças, o que torna difícil para a equipe e a família aceitarem o prognóstico limitado (24) , sendo necessário aos envolvidos (equipe assistencial e família) possuírem conhecimento acerca do processo de morrer do bebê, compreendendo o "como, onde e porque" (6,25) .…”
Section: Experienciando Cuidados Paliativosunclassified